Monitoring Gut Epithelium Serotonin and Melatonin Overflow Provides Spatial Mapping of Inflammation. (2nd December 2022) - Perez, Fernando; Kotecha, Nikki; Lavoie, Brigitte; Mawe, Gary M.; Patel, Bhavik Anil
Abstract: Electrochemical arrays were used to measure the overflow of serotonin (5‐HT) and melatonin (MEL) from the entire colon of healthy mice and mice with chemical‐induced inflammatory bowel disease (IBD), to understand the interplay between inflammation and colonic function. We show that 5‐HT overflow is increased, whilst MEL levels are reduced, in inflamed tissues. The levels of MEL are increased at the interface between healthy and inflamed regions within the colon and may limit the spread of inflammation. Understanding the interplay between inflammation and mucosal epithelial signalling can provide key insight into colonic function and aid the development of effective therapeutic strategies to treat gastrointestinal diseases. Abstract : Serotonin and melatonin play critical roles in regulating gut motility, but also have a key influence on the inflammatory status of the gut. The overflow of serotonin and melatonin provided spatial mapping of inflamed regions within the colon. This finding provides new insight into the tracking and therapeutic management of inflammatory bowel disorders.